ORGANIZATIONAL CULTURE AND TRAINING AS DETERMINANTS OF EMPLOYEE PERFORMANCE IMPROVEMENT IN THE VUCA ERA - Teguh Setiawan Wibowo; Helmina Br. Ginting; Budi Akhmad Tarigan; Swasta Bangun; Metha Djuwita Supriatna (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This research is motivated by the low performance of employees. This study aims to determine and analyze the influence of organizational culture and training on employee performance in the VUCA era. The research method used in this research is descriptive method with a quantitative approach. The sample in this study were 100 employees using random sampling technique. Data collection uses a questionnaire distributed via google form. The instruments used have been tested for validity and reliability. The collected data were analyzed using the classical assumption test and multiple linear regression using excel and SPSS. The results of this study indicate that 1) organizational culture has a positive and significant effect on employee performance in the VUCA era, 2) training has a positive and significant effect on employee performance in the VUCA era, and 3) organizational culture and training has a positive and significant effect on employee performance in the VUCA era. The findings of this study indicate that if companies want to improve employee performance in the VUCA era, companies must improve good organizational culture and provide training to employees.